Onrechmatige Daad and Default on Supreme Court Decision Number: Number: 1120 K / Pdt/2022 Jo. Number: 342 / Pdt / 2021 / PT MDN 342 / Pdt / 2021 / PT MDN. - Purnomo, Sigit; Saputra, Rilawadi; Kusbianto, Kusbianto (Universitas Dharmawangsa, 2024)
Procurement agreements have a very important function in the development of the country's economy, the amount of state money involved in this agreement is very large. Failure to fulfill this feat is often the basis for the injured party not to execute the agreement. The existence of parties who do not run the agreement often arise disputes because there are parties who feel disadvantaged as a result of this. The purpose of this research is to: 1). Describe the form of unlawful acts and defaults in the implementation of the procurement of goods and services in the decision of the Supreme Court Number: 1120 K/Pdt/2022 Jo. Decision number: 342/Pdt/2021 / PT MDN, 2). Reviewing legal considerations by judges in Supreme Court decision number: 1120 K/Pdt/2022 Jo. Decision number: 342/Pdt/2021 / PT MDN, 3). Reviewing the legal settlement of disputes over the procurement of goods and services that are not in accordance with the agreement on the Supreme Court decision number: 1120 K/Pdt/2022 Jo. No.342 / Pdt / 2021 / PT MDN. This type of research is normative legal research the data source of this research is secondary data, which includes: primary legal materials, secondary legal materials and tertiary legal materials. The method of data collection using the study of literature and documents. Analysis of research data using normative analysis of research results obtained a conclusion that: 1). Form of tort and tort in the Procurement Agreement of goods and services with number: PJJ.04.04.01/05/07/2019/0104 about the procurement and installation of AC (Air Conditioner) at Garbarata Kualanamu Deli Serdang International Airport in the Supreme Court decision number: 1120 K/Pdt/2022 Jo. No.342/Pdt/2021/PT MDN is the plaintiff/comparator/applicant for Cassation I / respondent to Cassation II (CV. Marendal Mas) is considered to have done what was promised, but it is too late and the defendant/compared/applicant Cassation II / respondent Cassation I (PT. Angkasa Pura II Kualanamu Airport Branch) did not immediately make payment for the work that the plaintiff/comparator plaintiff/comparator/Cassation applicant I/Cassation respondent did, as a result CV. Marendal Mas felt aggrieved because he could not pay the working capital of the bank and declared bad loans and collateral threatened with auction.